CHAPTER 38 FORENSIC USE OF HEAVY MINERALS IN CIVIL AND CRIMINAL INVESTIGATIONS - Isphording W.C. (My University, 2007)
Extensive historic use has been made of heavy minerals in sedimentological and stratigraphic studies. More recently, heavy minerals have been utilised in a wide variety of forensic applications. Five examples are presented to show how heavy minerals have been used in a murder investigation, identify the source of groundwater contamination, quantify the volume of sediment deposited in a wetland area as a result of improper erosion control in an adjacent subdivision, identify the source and cause of the premature aircraft engine failure and in a case involving industrial sabotage. These examples illustrate well how a mineral component, which often comprises less than 1% of a typical sample, can provide the geoscientist with information that is critical in a wide variety of forensic investigations. © 2007 Elsevier B.V. All rights reserved.
Keywords: FORENSIC; GROUNDWATER CONTAMINATION; SABOTAGE